Elevated cerebrospinal fluid sodium in hypertensive human subjects with a family history of Alzheimer’s disease - Souza, Lucas A. C.; Trebak, Fatima; Kumar, Veena; Satou, Ryousuke; Kehoe, Patrick G.; Yang, Wei; Wharton, Whitney; Feng Earley, Yumei (Physiological genomics, 2020)
High salt (sodium) intake leads to the development of hypertension despite the fact that plasma sodium concentration ([Na + ]) is usually normal in hypertensive human patients. Increased cerebrospinal fluid (CSF) sodium contributes to elevated sympathetic activity and high blood pressure (BP) in rodent models of hypertension. However, whether there is an increased accumulation of sodium in the CSF of humans with chronic hypertension is not well defined. Here, we investigated CSF [Na + ] from hypertensive and normotensive human subjects with family histories of Alzheimer’s disease in samples collected in a clinical trial, as spinal tap is not a routine clinical procedure for hypertensive patients. The [Na + ] and osmolality in plasma and CSF were measured by flame photometry. Daytime ambulatory BP was monitored while individuals were awake. Participants were deidentified and data were analyzed in conjunction with a retrospective analysis of patient history and diagnosis. We found that CSF [Na + ] was significantly higher in participants with high BP compared with normotensive participants; there was no difference in plasma [Na + ], or plasma and CSF osmolality between groups. Subsequent multiple linear regression analyses controlling for age, sex, race, and body mass index revealed a significant positive correlation between CSF [Na + ] and BP but showed no correlation between plasma [Na + ] and BP. In sum, CSF [Na + ] was higher in chronic hypertensive individuals and may play a key role in the pathogenesis of human hypertension. Collectively, our findings provide evidence for the clinical significance of CSF [Na + ] in chronic hypertension in humans.